PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN IMPLEMENTASI CSR SEBAGAI VARIABEL PEMODERASI - Munir, Misbahul; Suryandari, Eka Sevia; Mahmudah, Anik (IQTISHODUNA, 2014)
Corporate Governance is a system that regulates and controls the company that is expected toprovide and enhance the companyâs value to its shareholders. This study aims to determine the effect of theimplementation of good corporate governance (GCG) to the value of state-owned banks companies listings inIndonesia stock exchange (IDX) with the implementation of corporate social responsibility (CSR) as a moderatingvariable. This research is a quantitative, analytical models using classical assumption test consists of a testheterokedastisitas, non-autocorrelation test and normality test, followed by analysis using regression analysismoderation. The results showed that, application of good corporate governance is proxied by ManagerialOwnership (X1), Proportion of Independent Commissioner (X2), Audit Committee (X3), Independence of theAudit Committee (X4), Frequency of Audit Committee Meetings (X5) and the frequency of Board Meeting(X5) simultaneously significant effect on firm value (Tobinâs Q). With the results of R Square of 61.1% meansthat the variable Tobinâs Q (Y) in the six variables explained by the moderating variable of Corporate SocialResponsibility (Z). While the remaining 38.9% is explained by other variables or independent variables outsidethe regression equation.